2017
DOI: 10.1128/aac.01745-16
|View full text |Cite
|
Sign up to set email alerts
|

Classical β-Lactamase Inhibitors Potentiate the Activity of Daptomycin against Methicillin-Resistant Staphylococcus aureus and Colistin against Acinetobacter baumannii

Abstract: We asked whether beta-lactamase inhibitors (BLIs) increased the activity of daptomycin (DAP) against methicillin-resistant Staphylococcus aureus (MRSA), the peptide antibiotic colistin (COL) against the emerging Gram-negative nosocomial pathogen Acinetobacter baumannii, and the human host defense peptide cathelicidin LL37 against either pathogen. DAP and LL37 kill curves were performed with or without BLIs against MRSA, vancomycin-intermediate S. aureus (VISA), and heterogeneous VISA (hVISA). COL and LL37 kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
1
32
0
1
Order By: Relevance
“…When compared with the lack of in vivo activity demonstrated by avibactam, a non-β-lactam-BLI, our findings further suggest that binding to the organism's PBPs is required for tazobactam activity against A. baumannii. This influence on PBP activity likely alters the bacterial surface, rendering it more susceptible to endogenous antimicrobial peptides like cathelicidins that are present at very high concentrations in sites of infection [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared with the lack of in vivo activity demonstrated by avibactam, a non-β-lactam-BLI, our findings further suggest that binding to the organism's PBPs is required for tazobactam activity against A. baumannii. This influence on PBP activity likely alters the bacterial surface, rendering it more susceptible to endogenous antimicrobial peptides like cathelicidins that are present at very high concentrations in sites of infection [14].…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that β-lactam-BLIs provide additional collateral antibacterial activity by enhancing the activities of administered peptide antibiotics such as daptomycin against MRSA and colistin against A. baumannii, and even endogenous peptide antibiotics such as cathelicidin LL37 that are produced by the innate immune system against these pathogens [14]. While the activity of sulbactam, another β-lactam-BLI, alone has been characterized against some strains of A. baumannii, tazobactam has been less extensively studied against A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional ␤-lactamase inhibitors (BLIs) are themselves BL compounds that act as suicide substrates for the ␤-lactamases, rendering them inactive, thus protecting penicillins (e.g., penicillin, ampicillin [ (17). In addition, in a pharmacokinetic/pharmacodynamic in vitro hollow fiber model, we demonstrated that the addition of TAZ enhanced the synergy between ceftolozane (TOL) and DAP against MRSA (9).…”
mentioning
confidence: 91%
“…However, the resistance mechanisms of Staphylococcus spp. to these antibiotics have been also described today (Rybak et al, 2014;Miller et al, 2016;Sakoulas et al, 2017). Monitoring of the level of resistance both to traditional preparations and to the new ones is an important element in formation of a strategy of rational antibacterial therapy of infections caused by MRSA.…”
Section: Introductionmentioning
confidence: 99%